Nurturing a gender-responsive approach to climate-smart agriculture in Guinayangan, Quezon - Rosimo, Magnolia M.; Gonsalves, Julian Francis; Villavicencio, Francia (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Coconut-based farming systems in Guinayangan, Quezon offer special opportunities for achieving multiple objectives, including carbon sequestration, economic empowerment of women and reduction of risks from variable and extreme weather. This info note discusses the gender-based role inequalities within coconut-based farming systems that can be addressed through agroforestry-based, climate-smart agriculture that features small livestock, fruit trees and root and tuber crops as understory crops. Numerous Climate-Smart Villages, spread across the municipality of Guinayangan, now serve as proof of concept, providing evidence that climate-smart agriculture based on agroforestry interventions are gender sensitive.